2016
DOI: 10.1016/j.ccell.2016.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Interfering with CCL5/CCR5 at the Tumor-Stroma Interface

Abstract: In this issue of Cancer Cell, Halama et al. (2016) further advance chemokine interference as a therapeutic option for cancer by demonstrating the effect of CCR5 blockade in reshaping macrophage polarization toward an anti-tumor functional state in patient-derived tumor models and liver metastases of colorectal cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 11 publications
(21 reference statements)
0
12
0
Order By: Relevance
“…There are reports shown that fibroblasts involve in the cross-talk of cancer cells and fibroblasts by secreting CCL2 [3032], CCL5 [33], CXCL1 [34], CXCL6 [35], CXCL12 [36], IL6 [37], CXCL16 [38] and others [2331]. In the study, we identified that CCL11 and CXCL14 were the target genes of miR-29b in fibroblasts.…”
Section: Discussionmentioning
confidence: 79%
“…There are reports shown that fibroblasts involve in the cross-talk of cancer cells and fibroblasts by secreting CCL2 [3032], CCL5 [33], CXCL1 [34], CXCL6 [35], CXCL12 [36], IL6 [37], CXCL16 [38] and others [2331]. In the study, we identified that CCL11 and CXCL14 were the target genes of miR-29b in fibroblasts.…”
Section: Discussionmentioning
confidence: 79%
“…The pro-tumorigenic function of CCR5 is primarily mediated by it ligand CCL5, which promotes proliferation of CCR5-positive tumor cells, recruits immunosuppressive T-regulatory cells and favors metastasis (39). Hence, the CCL5/CCR5 axis has become a potential target for development of novel anticancer therapy (40,41). Arthrosclerosis is increasingly recognized to be a chronic inflammatory disease that involves leukocytes, such as monocytes/macrophages and T cells (42).…”
Section: Discussionmentioning
confidence: 99%
“…The CCL5/CCR5 axis is a potential therapeutic target in different cancer types. Since several studies have demonstrated its involvement in GC progression [ 48 , 101 , 106 , 110 ], counteracting the pro-tumorigenic effects of the CCL5/CCR5 axis with CCR5-antagonists, such as MVC [ 53 , 111 ], or alternatively, with drugs that are capable to of decreasing CCL5 secretion [ 69 ] may be a new therapeutic options for GC treatment.…”
Section: Possible Clinical Applications Of Mvc In Gcmentioning
confidence: 99%